Basking shark (Cetorhinus maximus) occurrence in relation to zooplankton abundance in the eastern Adriatic Sea - Soldo, Alen; Lučić, Davor; Jardas, Ivan (Société Française d'Ichtyologie, 2008)
Basking shark is a rather rare but constantly present species in the eastern Adriatic Sea. However, over the period 2000-2002 their occurrence in that area highly increased. Based on previous presumption, this paper investigates relations between zooplankton abundance and basking shark occurrence. It appears that increased shark occurrence is not directly influenced by changes in temperature and salinity. However, obtained data suggest relative importance of copepods, especially of Calanus helgolandicus, in relation to the occurrence of basking sharks.